Real-Time Data Integrity Validation Using Blockchain for Autonomous Vehicles - Raghavendra Kurva (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for implementing blockchain-based data integrity validation in autonomous vehicles. The proposed system addresses critical challenges in securing real-time sensor data through a hybrid architecture combining Hyperledger Fabric with Apache Kafka. By integrating distributed ledger technology with optimized data processing mechanisms, the system achieves both security and performance requirements essential for autonomous vehicle operations. The architecture incorporates smart contracts for data validation, multi-layered security protocols, and efficient data streaming capabilities. Results demonstrate that the proposed solution successfully balances the competing demands of data security and real-time processing, making it suitable for deployment in production autonomous vehicle environments.
Keywords: Blockchain Security; Autonomous Vehicles; Data Integrity; Real-time Processing; Distributed Ledger Technology